Engendering Transnational Foodways: A Case Study of Southern Sudanese Women in Brooks, Alberta: Graduate Student Papers in Feminist Anthropology Award - Oleschuk, Merin (Anthropologica, 2022)
This article explores the experiences of Southern Sudanese refugee women in Brooks, Alberta, illustrating how "foodways" (Long 2004) impact and reflect women's conceptions of themselves as gendered, multinational citizens. When women seek out and appropriate diverse culinary traditions to create belonging within multiple circumstances, they enact agency. Women do not passively accept their fractured connections to their homeland but instead actively work to rebuild relation ships within the diversity that defines their experiences in ways that garner them power, prestige and resources to improve their lives. These movements show how gender and power are en twined in the creation of transnational belonging.